Until When Silent Cries of Pakistani Marginalized Youth Would Remain Unaddressed – A Thematic Short Review through the Lens of Subjective Well-Being - Muhammad Saleem, Muhammad Saleem; Ismail, Dr Rozmi; Zakaria, Dr. Ezarina; Che Kasim, Dr. Arena (School of Social Sciences, 2015)
The overarching aim of this thematic short review is to highlight the paucity of mental health research available for marginalized youth living in Pakistan. To establish a research gap, seven most relevant documents available on current plight of Pakistani youth has been selected randomly that comprised of project reports, journal articles and narrative essays. The span of documents ranged from 2004 to 2014. For review, an unsorted literature matrix has been furnished with keeping in view some systematic steps in order. Findings of all documents further categorized into two main themes (Adversity & Demographic Bonus) and four subthemes (marginalization; street violence; radicalization; & psychological issues). On the one hand, it is anticipated from findings that Pakistani youth experiencing variety of adversities that may lead towards loss of subjective well-being. On the other hand, this youth entered in the arena of demographic bonus that can be fruitful for positive nation building, if current youth is channelized well. The scarcity of research particularly on ‘Pakistani marginalized youth’ is a big question mark for local and international research communities that direly demand to be addressed.